A titanium-based enamel coating suitable for low-temperature firing and a preparation method thereof
By using low-temperature firing technology in the preparation of titanium-based enamel coatings, combined with the specific formula and spraying process of enamel glaze slurry, the problems of reduced binding force and limited application areas caused by high-temperature firing are solved, and the titanium-based enamel coating with high binding force and temperature resistance are achieved, expanding its application in other fields.
Patent Information
- Application Number
- CN202510174638.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-18
AI Technical Summary
During the high-temperature sintering process of existing titanium-based enamel coatings, the crystal form transformation, volume expansion and thermal stress of the titanium substrate are increased, affecting the binding force between the coating and the substrate, and the high firing temperature limits its application in other fields.
The preparation method of titanium-based enamel coating with low temperature firing is adopted. By mixing the enamel frit, clay, nitros and water in a specific proportion, an enamel glaze slurry is formed, and then sprayed on the surface of TA1 titanium substrate in an oven at 100~110 ℃, and then fired in a high-temperature furnace at 740~840 ℃ for 10~15 min to produce a titanium-based enamel coating with excellent binding force and temperature resistance.
It effectively reduces the firing temperature, reduces energy loss, avoids volume expansion and thermal stress caused by crystal form transformation of titanium substrates, improves the binding force between the coating and the substrate and temperature-resistant rapid change performance, and expands the application of titanium alloys in other fields.
Smart Images

Figure CN119638197B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of enamel material preparation and application, and particularly relates to an enamel coating suitable for low-temperature sintering on the surface of a titanium alloy substrate and a preparation method thereof. Background Art
[0002] Titanium metal has two allotropes, that is, below 882 ° C, titanium has a close-packed hexagonal structure (α-Ti), and above 882 ° C, titanium has a body-centered cubic structure (β-Ti). Titanium alloys have high specific strength, specific stiffness, excellent corrosion resistance, and good biocompatibility. They have been widely used in aerospace, marine development, medical treatment, petrochemicals, industrial corrosion protection, and daily tableware. However, titanium alloys are very easy to absorb hydrogen, and a small amount of hydrogen adsorption can cause titanium alloys to become brittle or crack. Titanium alloys are easily oxidized at high temperatures to form a hard and brittle oxygen-rich layer, which also limits the application and development of titanium alloys to a certain extent.
[0003] In order to improve the surface properties of titanium alloy, researchers modified the alloy surface with coating. Enamel is an inorganic non-metallic material. By regulating the composition of enamel frit, it can be firmly bonded with most metals to form an inert oxide coating. Enamel coating has excellent chemical stability, fire resistance, heat resistance, high temperature resistance, corrosion resistance and other characteristics. At the same time, it has a simple manufacturing process and low production cost.
[0004] The existing titanium-based enamel has a high content of oxides with low expansion coefficients such as silicon oxide, zirconium oxide, and titanium oxide, which means that the enamel has a high softening temperature, a low thermal expansion coefficient, and a high firing temperature. Most of the existing patents are aimed at the application of titanium-based enamel coatings in the aerospace field, aiming to improve high-temperature oxidation resistance, chemical corrosion resistance, and thermal shock resistance, and the firing temperature is 900~1100 ℃. Patent CN107601882A discloses an enamel coating for titanium alloy and a preparation method thereof, with a firing temperature of 900~950 ℃, and the thermal shock resistance temperature of the coating is higher than 600 ℃. Patent CN105439450A discloses a titanium alloy enamel coating material and a preparation method thereof, using TC4 alloy as the substrate, with a firing temperature of 950 ℃, and having good high-temperature oxidation resistance and thermal shock resistance. Patent CN101215710A discloses a glassy barrier layer for titanium or titanium alloy to prevent hydrogen or hydrogen isotope penetration and its preparation method. The enamel is fired at 900~1100℃ for 15~30 min, the coating thickness is 50~180 μm, and there is no crack after 50 times of water cooling at 550℃. It has a strong barrier effect to prevent hydrogen isotope penetration. Patent CN104193173A discloses a titanium alloy surface fired enamel insulation coating material and its preparation method. The firing temperature is 900~1000℃. The enamel coating has excellent resistance to high temperature oxidation, molten salt corrosion, and temperature change resistance at 360~420℃.
[0005] An analysis of the technical solutions disclosed in the above-mentioned existing patents shows that high firing temperatures bring the following problems: (1) When the firing temperature is higher than 882.5°C, the crystal structure of titanium changes from a close-packed hexagonal structure (α-Ti) to a body-centered cubic structure (β-Ti), resulting in volume expansion, thereby increasing the difference in thermal expansion coefficients between the coating and the titanium substrate, causing greater thermal stress to accumulate between the coating and the substrate, thereby affecting the bonding between the two. (2) High temperatures enhance the interface reaction between the titanium substrate and the enamel, generating more brittle silicide Ti. x Si y , resulting in a decrease in the bonding strength between the coating and the substrate. (3) The high firing temperature limits the application of titanium-based enamel coatings in other fields, such as petrochemicals, industrial corrosion protection, and daily tableware. In order to solve the above problems, the present invention proposes a titanium-based enamel coating suitable for low-temperature firing and a preparation method thereof. Summary of the invention
[0006] The purpose of the present invention is to provide a titanium-based enamel coating suitable for low-temperature sintering, having good bonding strength and excellent temperature-surge resistance and a preparation method thereof to solve the problems raised in the background technology and expand the application of titanium alloys in other fields.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a titanium-based enamel coating suitable for low-temperature firing comprises the following steps:
[0009] (1) According to the mass percentage, 100% of enamel frit, 6% of clay, 0.15% of nitrite and 35% of water are mixed to obtain enamel glaze slurry;
[0010] (2) pretreating the surface of the TA1 titanium substrate, and then spraying the enamel slurry prepared in step (1) on the surface of the substrate;
[0011] (3) placing the substrate coated with the enamel slurry obtained in step (2) in an oven at 100-110° C. and drying for 20-30 minutes;
[0012] (4) After being completely dried, the substrate is placed in a high-temperature furnace at 740-840 °C and fired for 10-15 min to obtain a titanium-based enamel coating with excellent bonding strength and resistance to sudden temperature changes.
[0013] Preferably, the method for preparing the enamel frit comprises the following steps:
[0014] (1.1) According to mass percentage, 28-47.7% of quartz, 21.2-46.4% of boric acid, 10.5-13.6% of soda ash, 5.4-6.9% of lithium carbonate, 3.8-4.4% of zinc oxide, 1.8-3.0% of barium carbonate, 2.6-5.5% of strontium carbonate and 0.5-1.0% of zirconium quartz powder are mixed to obtain a batch material;
[0015] (1.2) The batch material is melted in an electric furnace with silicon-molybdenum rods at 1500-1600 °C for 60-120 min. The molten mixture is quenched in water and dried to obtain an enamel frit.
[0016] Preferably, the enamel slurry is obtained by ball milling process.
[0017] Preferably, the pretreatment in step (2) specifically refers to: polishing the surface of the TA1 titanium substrate with 40-mesh sandpaper, then ultrasonically cleaning it with anhydrous ethanol and deionized water for 20 to 40 minutes in sequence, and after cleaning, drying it with compressed air.
[0018] Preferably, the thickness of the titanium-based enamel coating prepared in step (4) is 100-115 μm.
[0019] The present invention further protects a titanium-based enamel coating suitable for low-temperature firing and prepared by the above method.
[0020] Compared with the prior art, the present invention provides a titanium-based enamel coating suitable for low-temperature sintering and a preparation method thereof, which has the following beneficial effects:
[0021] (1) The enamel coating prepared by the present invention has a temperature of 740-840°C, which is 160-260°C lower than that of the prior art, effectively reducing energy loss in the preparation process, achieving sintering below the allotropic transformation temperature of titanium (882.5°C), avoiding volume expansion caused by crystal transformation of the titanium substrate during high-temperature sintering, reducing thermal stress between the coating and the titanium substrate, and avoiding the technical problem of decreased mechanical properties of the substrate caused by excessively high sintering temperature.
[0022] (2) The enamel coating prepared by the present invention has good matching of thermal expansion coefficient with TA1 titanium substrate, excellent bonding strength, excellent resistance to sudden temperature change, and can withstand the impact of water-cooled temperature difference of 700°C. The enamel coating can effectively protect the titanium substrate and extend its service life.
[0023] (3) The preparation method proposed in the present invention has a simple process and a wide sintering temperature range, is suitable for industrial production, and can be expanded to other application fields of titanium alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1This is a flow chart of the method for preparing the titanium-based enamel coating suitable for low-temperature sintering proposed by the present invention;
[0025] Figure 2 This is a nanoindentation microhardness distribution diagram of the enamel coating prepared in Example 1 of the present invention at the interface between the TA1 titanium substrate and the enamel;
[0026] Figure 3 This is a macroscopic morphology of the surface cracking of the titanium-based enamel coating prepared in Comparative Example 3 of the present invention after drying;
[0027] Figure 4 This is an optical microscope image of the enamel coating prepared in Example 2 of the present invention at the interface between the TA1 titanium substrate and the enamel;
[0028] Figure 5 The macroscopic morphology of the enamel coating prepared in Example 3 of the present invention and the optical microscope image of the interface between the TA1 titanium substrate and the enamel;
[0029] Figure 6 This is a SEM image of the enamel coating prepared in Example 3 of the present invention at the interface between the TA1 titanium substrate and the enamel;
[0030] Figure 7 This is the EDS element distribution diagram of the enamel coating at the interface between the TA1 titanium substrate and the enamel in Example 5 of the present invention;
[0031] Figure 8 This is an optical microscope image of the enamel coating prepared in Example 6 of the present invention at the interface between the TA1 titanium substrate and the enamel;
[0032] Fig. 9 This is a nanoindentation microhardness distribution diagram of the enamel coating prepared in Example 7 of the present invention at the interface between the TA1 titanium substrate and the enamel;
[0033] Fig.10 This is the nanoindentation microhardness distribution diagram of the enamel coating prepared in Comparative Example 8 at the interface between the TA1 titanium substrate and the enamel;
[0034] Fig.11 This is the EDS element distribution diagram of the enamel coating of comparative example 8 at the interface between the TA1 titanium substrate and the enamel. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0036] First, the design idea of the present invention is described:
[0037] The present invention provides a titanium-based enamel coating suitable for low-temperature firing and a preparation method thereof. In terms of reducing the firing temperature of the enamel, the most important thing is the reasonable ratio of the enamel formula components. Clay, nitrite and water are used to improve the suspension of the enamel glaze slurry to obtain good spraying performance. By optimizing the firing process, the enamel and the TA1 substrate form a good combination at a lower firing temperature to meet the use requirements.
[0038] In the enamel formula, there is a synergistic effect between the components, and they also affect each other. While reducing the firing temperature, it is also necessary to ensure that the enamel has a small expansion coefficient so that it matches the titanium substrate. The present invention uses Na2O-B2O3-SiO2 as a matrix, wherein SiO2 is used as a network former. The higher its content, the higher the continuity of the silicon-oxygen network, and the macroscopic performance is that the firing temperature is high. B2O3 can be used as a network former and is also a good flux, which can enhance the wettability of enamel on the substrate surface. As a flux, Na2O can break the silicon-oxygen network of the enamel frit and divide it into many small groups of varying sizes, which leads to a significant increase in the expansion coefficient while the firing temperature is reduced. Therefore, by utilizing the mixed alkali effect, lithium oxide is introduced into the formula. A small amount of lithium oxide accumulates due to lithium ions and occupies the network gap after disconnection, making the network structure dense, and it does not cause volume expansion while reducing the firing temperature. The introduction of alkaline earth metal oxides strontium oxide and barium oxide has a certain aggregation effect on the broken silicon oxygen network, thereby reducing the increase in the expansion coefficient and improving the high temperature strength and high temperature stability of the enamel coating. A small amount of ZrO2 is introduced to adjust the expansion coefficient.
[0039] See also Figure 1 The method for preparing a titanium-based enamel coating suitable for low-temperature sintering proposed by the present invention comprises the following steps:
[0040] (1) 28-47.7% of quartz, 21.2-46.4% of boric acid, 10.5-13.6% of soda ash, 5.4-6.9% of lithium carbonate, 3.8-4.4% of zinc oxide, 1.8-3.0% of barium carbonate, 2.6-5.5% of strontium carbonate, and 0.5-1.0% of zircon quartz powder are mixed to obtain an enamel frit batch;
[0041] (2) The batch materials of the enamel frit are placed in a crucible and melted in an electric furnace with a silicon-molybdenum rod at 1550°C for 60-120 min. The enamel melt is drawn with a metal rod. After the drawn wire is tested to have no nodules within 1 m, the melt is poured into water for water quenching and dried to obtain the enamel frit.
[0042] (3) According to the mass percentage, enamel frit 100%, clay 6%, nitrite 0.15%, water 35%, by ball milling process, through 60 mesh sieve, to prepare enamel glaze slurry;
[0043] (4) Pre-treating the surface of the TA1 titanium substrate: first, polishing the surface of the TA1 titanium substrate with 40-grit sandpaper, then ultrasonically cleaning it with anhydrous ethanol and deionized water for 30 min in sequence, and then drying it with compressed air;
[0044] (5) The enamel slurry prepared according to (3) was wet-sprayed on the surface of the pretreated TA1 titanium substrate. The substrate coated with the enamel slurry was placed in an oven at 100-110 °C for 20-30 min. After being completely dried, the substrate was placed in a high-temperature furnace at 740-840 °C for 10 min to obtain a titanium-based enamel coating with excellent bonding strength and temperature shock resistance.
[0045] The preparation method of the titanium-based enamel coating suitable for low-temperature sintering proposed by the present invention is further described below in conjunction with relevant drawings and specific examples. The specific contents are as follows.
[0046] Embodiment 1:
[0047] A method for preparing a titanium-based enamel coating suitable for low-temperature firing, comprising the following contents:
[0048] (1) The enamel frit is prepared by mixing, by mass percentage, 28% quartz, 46.4% boric acid, 10.5% soda ash, 6.0% lithium carbonate, 3.8% zinc oxide, 1.8% barium carbonate, 2.6% strontium carbonate and 0.9% zirconium quartz powder to obtain a batch material.
[0049] (2) The batch material is melted in an electric furnace with silicon-molybdenum rods at 1550 °C for 60 min. The melted mixture is quenched in water and dried to obtain an enamel frit.
[0050] (3) Prepare, by mass percentage, 100% enamel frit, 6% clay, 0.15% nitrite and 35% water, ball mill for 15 min, and sieve through 60 mesh to obtain enamel slurry.
[0051] (4) The surface of the TA1 titanium substrate was polished with 40-grit sandpaper and ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min respectively. After cleaning, it was blown dry with compressed air.
[0052] (5) The enamel slurry prepared according to (3) was wet-sprayed on the surface of the pretreated TA1 titanium substrate. The substrate coated with the enamel slurry was placed in an oven at 100 °C for 30 min. After being completely dried, the substrate was placed in a high-temperature furnace at 740 °C for 10 min.
[0053] (6) The final titanium-based enamel layer is about 100 μm thick and the firing temperature is 740 °C.
[0054] (7) The temperature change test of enamel starts from 200 °C, keeps warm for 30 minutes, and then quickly puts it in 25 °C water. After wiping it with a cloth, observe the damage of the coating. If the coating is intact, increase the temperature by 50 °C each time. After reaching 450 °C, increase the temperature by 25 °C each time until the porcelain layer peels off and stops the test. The temperature change resistance temperature is the difference between the temperature before the first peeling and the water temperature. The temperature change resistance temperature of the titanium-based enamel layer in this embodiment is 700 °C.
[0055] (8) The bonding strength between the enamel coating and the metal substrate was evaluated by an impact resistance test of the enamel. A 200 g steel ball was used to vertically impact the titanium-based enamel coating prepared in this example from a height of 1 m. Ring-shaped cracks appeared on the surface, but no peeling of the ceramic layer was observed.
[0056] (9) The enamel coating prepared in this example was subjected to a high-speed nanoindentation test. The nanoindentation microhardness distribution of the interface between the TA1 titanium substrate and the enamel was as follows: Figure 2 As shown. Figure 2 It can be seen that the interface hardness of the titanium-based enamel coating prepared in this embodiment is distributed in a gradient manner, the hardness gradually decreases from the enamel layer to the TA1 titanium substrate, and there is a transition layer in the interface hardness.
[0057] Comparative Example 1:
[0058] Based on Example 1, but with the difference that the enamel glaze slurry is prepared by mass percentage, enamel frit 100%, clay 3%, nitrite 0.15% and water 35%, ball milling for 15 min, and sieving through 60 mesh to obtain the enamel glaze slurry. The enamel glaze slurry has low viscosity and poor retention. During the transportation process of the sprayed sample into the oven, the glaze slurry flows when slightly stressed, and the surface thickness is uneven after firing. The main reason is that the clay content in the glaze slurry is low, the bound water and adsorbed water formed after the clay is hydrated are relatively small, and the water in the glaze slurry exists mostly in the form of free water, which flows when slightly disturbed.
[0059] Comparative Example 2:
[0060] Based on Example 1, but different in that the enamel glaze slurry is prepared by mass percentage, enamel frit 100%, clay 6%, nitrite 0.05% and water 35%, ball milling for 15 min, and sieving through 60 mesh to obtain the enamel glaze slurry. The enamel glaze slurry has poor suspension and is easy to settle. The gun is easy to block when the glaze slurry is sprayed, the operability is poor, and the surface uniformity of the sample after spraying is poor. The main reason is that the electrolyte content in the glaze slurry is low. In the suspension system formed by enamel particles, electrolytes and clay, the repulsion between particles is small, and the glaze slurry is easy to settle.
[0061] Comparative Example 3:
[0062] Based on Example 1, the difference is that the enamel slurry is prepared by ball milling according to the mass percentage of enamel frit 100%, water glass 14%, and water 35%. The surface of the enamel coating is cracked after drying, and the macroscopic morphology is as follows Figure 3 The main reason is that there are too many soluble salts and aqueous solutions in the glaze slurry, which leads to the reduction of the powder embryo strength of the enamel coating after drying. The powder embryo cracks due to stress concentration and cannot form a continuous enamel coating after firing.
[0063] Embodiment 2:
[0064] A method for preparing a titanium-based enamel coating suitable for low-temperature firing, comprising the following contents:
[0065] (1) The enamel frit is prepared by mixing 32.6% quartz, 38.6% boric acid, 10.5% soda ash, 5.4% lithium carbonate, 4.0% zinc oxide, 2.8% barium carbonate, 5.5% strontium carbonate and 0.5% zirconium quartz powder in percentage by mass to obtain a batch material.
[0066] (2) The batch material is melted in an electric furnace with silicon-molybdenum rods at 1550 °C for 70 min. The melted mixture is quenched in water and dried to obtain an enamel frit.
[0067] (3) Prepare, by mass percentage, 100% enamel frit, 6% clay, 0.15% nitrite and 35% water, ball mill for 15 min, and sieve through 60 mesh to obtain enamel slurry.
[0068] (4) The surface of the TA1 titanium substrate was polished with 40-grit sandpaper and ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min respectively. After cleaning, it was blown dry with compressed air.
[0069] (5) The enamel slurry prepared according to (3) was wet-sprayed on the surface of the pretreated TA1 titanium substrate. The substrate coated with the enamel slurry was placed in an oven at 100 °C for 30 min. After being completely dried, the substrate was placed in a high-temperature furnace at 780 °C for 10 min.
[0070] (6) The final titanium-based enamel layer is about 105 μm thick and the firing temperature is 780 °C.
[0071] (7) The cross-sectional analysis of the enamel coating prepared in this example was performed, and the optical microscope results are as follows: Figure 4 As shown. Figure 4 It can be seen that the titanium-based enamel coating prepared in the present invention is tightly bonded to the interface.
[0072] Embodiment 3:
[0073] A method for preparing a titanium-based enamel coating suitable for low-temperature firing, comprising the following contents:
[0074] (1) The enamel frit is prepared by mixing, by mass percentage, 32.5% quartz, 41% boric acid, 10.9% soda ash, 6.2% lithium carbonate, 3.9% zinc oxide, 1.8% barium carbonate, 2.7% strontium carbonate and 0.9% zirconium quartz powder to obtain a batch material.
[0075] (2) The batch material is melted in an electric furnace with silicon-molybdenum rods at 1550 °C for 70 min. The melted mixture is quenched in water and dried to obtain an enamel frit.
[0076] (3) Prepare, by mass percentage, 100% enamel frit, 6% clay, 0.15% nitrite and 35% water, ball mill for 15 min, and sieve through 60 mesh to obtain enamel slurry.
[0077] (4) The surface of the TA1 titanium substrate was polished with 40-grit sandpaper and ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min respectively. After cleaning, it was blown dry with compressed air.
[0078] (5) The enamel slurry prepared according to (3) was wet-sprayed on the surface of the pretreated TA1 titanium substrate. The substrate coated with the enamel slurry was placed in an oven at 110 °C for 20 min. After being completely dried, the substrate was placed in a high-temperature furnace at 800 °C for 10 min.
[0079] (6) The thickness of the titanium-based enamel layer finally obtained is about 110 μm, and the firing temperature is 800 °C. The macroscopic morphology of the enamel coating and the optical microscope image of the interface between the TA1 titanium substrate and the enamel are shown in Figure 2. Figure 5 shown.
[0080] (7) The temperature change test of enamel starts from 200°C, keeps the temperature for 30 minutes, and then quickly puts it in 25°C water. After wiping it with a cloth, observe the damage of the coating. If the coating is intact, increase the temperature by 50°C each time. After reaching 450°C, increase the temperature by 25°C each time until the porcelain layer peels off and stop the test. The temperature change resistance temperature is the difference between the temperature before the first peeling and the water temperature. The titanium-based enamel layer in this embodiment can withstand a temperature change of 725°C.
[0081] (8) The bonding strength between the enamel coating and the metal substrate was evaluated by an impact test of the enamel. A 200 g steel ball was used to vertically impact the titanium-based enamel coating in Example 3 from a height of 1 m. The surface was mainly composed of annular cracks, with very few point fractures, and no shiny metal surface was exposed.
[0082] (9) The cross-sectional analysis of the enamel coating prepared in this example is shown in the SEM results. Figure 6 As shown. Figure 6 It can be seen that the titanium-based enamel coating prepared in the present invention has a lower porosity and a tight interface.
[0083] Embodiment 4:
[0084] A method for preparing a titanium-based enamel coating suitable for low-temperature firing, comprising the following contents:
[0085] (1) The enamel frit is prepared by mixing, in percentage by mass, 37.3% quartz, 35.1% boric acid, 11.3% soda ash, 6.4% lithium carbonate, 4.1% zinc oxide, 1.9% barium carbonate, 2.8% strontium carbonate and 1.0% zirconium quartz powder to obtain a batch material.
[0086] (2) The batch material is melted in an electric furnace with silicon-molybdenum rods at 1550 °C for 75 min. The molten mixture is quenched in water and dried to obtain an enamel frit.
[0087] (3) Prepare, by mass percentage, 100% enamel frit, 6% clay, 0.15% nitrite and 35% water, ball mill for 15 min, and sieve through 60 mesh to obtain enamel slurry.
[0088] (4) The surface of the TA1 titanium substrate was polished with 40-grit sandpaper and ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min respectively. After cleaning, it was blown dry with compressed air.
[0089] (5) The enamel slurry prepared according to (3) was wet-sprayed on the surface of the pretreated TA1 titanium substrate. The substrate coated with the enamel slurry was placed in an oven at 100 °C for 30 min. After being completely dried, the substrate was placed in a high-temperature furnace at 800 °C for 10 min.
[0090] (6) The final titanium-based enamel layer is about 110 μm thick and the firing temperature is 800 °C.
[0091] (7) The temperature change test of enamel starts from 200°C, keeps the temperature for 30 minutes, and then quickly puts it in 25°C water. After wiping it with a cloth, observe the damage of the coating. If the coating is intact, increase the temperature by 50°C each time. After reaching 450°C, increase the temperature by 25°C each time until the porcelain layer peels off and stop the test. The temperature change resistance temperature is the difference between the temperature before the first peeling and the water temperature. The titanium-based enamel layer in this embodiment can withstand a temperature change of 725°C.
[0092] (8) The bonding strength between the enamel coating and the metal substrate was evaluated by an impact resistance test of the enamel. A 200 g steel ball was used to vertically impact the titanium-based enamel coating in this embodiment from a height of 1 m. A small amount of point-like fractures appeared on the surface, and the shiny metal surface was not exposed.
[0093] Comparative Example 4:
[0094] Based on Example 4, but with a difference, the enamel frit is obtained by mixing and melting quartz 37.3%, boric acid 19.1%, soda ash 11.3%, lithium carbonate 6.4%, zinc oxide 4.1%, barium carbonate 7.9%, strontium carbonate 12.8%, and zircon quartz powder 1.0% by mass percentage. Microcracks can be observed in the prepared titanium-based enamel coating. The main reason is that the reduction of boric acid content and the increase of strontium carbonate and barium carbonate content lead to a reduction in the content of boron oxide, a network former, in the enamel, and the flux component barium oxide and strontium oxide content are too high. Here, boron oxide is mainly connected to the silicon oxygen network in the form of boron oxygen trihedrons through weak bonds such as hydrogen bonds to form a low melting point mixture, which relaxes the enamel network structure and increases the thermal expansion coefficient. Barium oxide and strontium oxide depolymerize the network, and since the ionic radius of barium ions and strontium ions is larger than the network gap, the network structure is expanded. The reduction in expansion coefficient brought about by the reduction of boron oxide is not enough to offset the network expansion caused by barium oxide and strontium oxide, which ultimately leads to an increase in the expansion coefficient of the enamel.
[0095] Comparative Example 5:
[0096] Based on Example 4, but with a difference, the enamel frit is obtained by mixing and melting quartz 37.3%, boric acid 32.4%, soda ash 14.1%, lithium carbonate 6.4%, zinc oxide 4.1%, barium carbonate 1.9%, strontium carbonate 2.8%, and zirconium quartz powder 1% by mass percentage. Cracks were observed in the prepared titanium-based enamel coating under a microscope. The main reasons are the reduction of boric acid content and the increase of sodium carbonate content, which leads to a reduction in the content of boron oxide, a network former in the enamel, an increase in the content of sodium oxide, a flux component, and an enhanced network breaking ability, which ultimately leads to a mismatch in the expansion coefficient between the enamel coating and the titanium substrate.
[0097] Comparative Example 6:
[0098] Based on Example 4, but the difference is that the enamel frit is mixed and melted by mass percentage, quartz 37.3%, boric acid 35.1%, soda ash 17.7%, zinc oxide 4.1%, barium carbonate 1.9%, strontium carbonate 2.8%, and zircon quartz powder 1% to obtain the enamel frit. Microcracks were observed in the prepared titanium-based enamel coating under a microscope. The main reason is that after lithium carbonate is completely replaced by sodium carbonate, the sodium oxide content in the flux component increases. Sodium oxide destroys the silicon-oxygen bond of the silicon-oxygen tetrahedron, making the network structure loose, and sodium ions occupy the grid gap, which is prone to volume expansion when heated. A small amount of lithium oxide does not cause the volume expansion of the silicon-oxygen network while reducing the melting temperature. Due to the small radius of the lithium ion, it fills the gap of the silicon-oxygen network and does not cause the expansion of the network structure. Therefore, lithium carbonate is completely replaced by sodium carbonate in the enamel frit, resulting in an increase in the enamel expansion coefficient.
[0099] Comparative Example 7:
[0100] Based on Example 4, but different in that, the enamel frit is mixed and melted to obtain the enamel frit with the following mass percentages: 37.3% quartz, 35.1% boric acid, 11.3% soda ash, 6.4% potassium carbonate, 4.1% zinc oxide, 4.7% calcium carbonate, and 1% zirconium quartz powder. The prepared titanium-based enamel coating can withstand a temperature shock of 500°C.
[0101] Embodiment 5:
[0102] A method for preparing a titanium-based enamel coating suitable for low-temperature firing, comprising the following contents:
[0103] (1) The enamel frit is prepared by mixing quartz 42.1%, boric acid 28%, soda ash 13.1%, lithium carbonate 6.7%, zinc oxide 4.3%, barium carbonate 2.0%, strontium carbonate 2.9% and zirconium quartz powder 1.0% in percentage by mass to obtain a batch material.
[0104] (2) The batch material is melted in an electric furnace with silicon-molybdenum rods at 1550 °C for 100 min. The melted mixture is quenched in water and dried to obtain an enamel frit.
[0105] (3) Prepare, by mass percentage, 100% enamel frit, 6% clay, 0.15% nitrite and 35% water, ball mill for 15 min, and sieve through 60 mesh to obtain enamel slurry.
[0106] (4) The surface of the TA1 titanium substrate was polished with 40-grit sandpaper and ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min respectively. After cleaning, it was blown dry with compressed air.
[0107] (5) The enamel slurry prepared according to (3) was wet-sprayed on the surface of the pretreated TA1 titanium substrate. The substrate coated with the enamel slurry was placed in an oven at 100 °C for 30 min. After being completely dried, the substrate was placed in a high-temperature furnace at 820 °C for 10 min.
[0108] (6) The final titanium-based enamel layer is about 110 μm thick and the firing temperature is 820 °C.
[0109] (7) The temperature change test of enamel starts from 200°C, keeps the temperature for 30 minutes, and then quickly puts it in 25°C water. After wiping it with a cloth, observe the damage of the coating. If the coating is intact, increase the temperature by 50°C each time. After reaching 450°C, increase the temperature by 25°C each time until the porcelain layer peels off and then stop the test. The temperature change resistance is the difference between the temperature before the first peeling and the water temperature. The temperature change resistance of the titanium-based enamel layer in this embodiment is 700°C.
[0110] (8) The bonding strength between the enamel coating and the metal substrate was evaluated by an impact test of the enamel. A 200 g steel ball was used to vertically impact the titanium-based enamel coating in this embodiment from a height of 1 m. The surface showed filamentous and point-like fractures, and the shiny metal surface was not exposed.
[0111] (9) EDS line scanning was performed on the enamel coating prepared in this example. The results are as follows: Figure 7 As shown. Figure 7 It can be seen that in the titanium-based enamel coating prepared by the present invention, there is diffusion of Si, Ti, and O elements at the interface between the TA1 titanium substrate and the enamel, and the interface bonding force is mainly chemical bond bonding.
[0112] Embodiment 6:
[0113] A method for preparing a titanium-based enamel coating suitable for low-temperature firing, comprising the following contents:
[0114] (1) The enamel frit is prepared by mixing quartz 42.2%, boric acid 27.2%, soda ash 11.8%, lithium carbonate 6.7%, zinc oxide 4.3%, barium carbonate 3.0%, strontium carbonate 4.4% and zirconium quartz powder 0.5% in percentage by mass to obtain a batch material.
[0115] (2) The batch material is melted in an electric furnace with silicon-molybdenum rods at 1550 °C for 100 min. The melted mixture is quenched in water and dried to obtain an enamel frit.
[0116] (3) Prepare, by mass percentage, 100% enamel frit, 6% clay, 0.15% nitrite and 35% water, ball mill for 15 min, and sieve through 60 mesh to obtain enamel slurry.
[0117] (4) The surface of the TA1 titanium substrate was polished with 40-grit sandpaper and ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min respectively. After cleaning, it was blown dry with compressed air.
[0118] (5) The enamel slurry prepared according to (3) was wet-sprayed on the surface of the pretreated TA1 titanium substrate. The substrate coated with the enamel slurry was placed in an oven at 100 °C for 30 min. After being completely dried, the substrate was placed in a high-temperature furnace at 820 °C for 10 min.
[0119] (6) The final titanium-based enamel layer is about 100 μm thick and the firing temperature is 820 °C.
[0120] (7) The cross-sectional analysis of the enamel coating prepared in this example was performed, and the optical microscope results are as follows: Figure 8 As shown. Figure 8 It can be seen that the titanium-based enamel coating prepared in this embodiment is tightly bonded to the interface.
[0121] Embodiment 7:
[0122] A method for preparing a titanium-based enamel coating suitable for low-temperature firing, comprising the following contents:
[0123] (1) The enamel frit is prepared by mixing, by mass percentage, 47.7% quartz, 21.2% boric acid, 13.6% soda ash, 6.9% lithium carbonate, 4.4% zinc oxide, 2.1% barium carbonate, 3.0% strontium carbonate and 1.0% zirconium quartz powder to obtain a batch material.
[0124] (2) The batch material is melted in an electric furnace with silicon-molybdenum rods at 1550 °C for 120 min. The melted mixture is quenched in water and dried to obtain an enamel frit.
[0125] (3) Prepare, by mass percentage, 100% enamel frit, 6% clay, 0.15% nitrite and 35% water, ball mill for 15 min, and sieve through 60 mesh to obtain enamel slurry.
[0126] (4) The surface of the TA1 titanium substrate was polished with 40-grit sandpaper and ultrasonically cleaned with anhydrous ethanol and deionized water for 30 min respectively. After cleaning, it was blown dry with compressed air.
[0127] (5) The enamel slurry prepared according to (3) was wet-sprayed on the surface of the pretreated TA1 titanium substrate. The substrate coated with the enamel slurry was placed in an oven at 100 °C for 30 min. After being completely dried, the substrate was placed in a high-temperature furnace at 840 °C for 10 min.
[0128] (6) The final titanium-based enamel layer is about 100 μm thick and the firing temperature is 840 °C.
[0129] (7) The temperature change test of enamel starts from 200°C, keeps the temperature for 30 minutes, and then quickly puts it in 25°C water. After wiping it with a cloth, observe the damage of the coating. If the coating is intact, increase the temperature by 50°C each time. After reaching 450°C, increase the temperature by 25°C each time until the porcelain layer peels off and then stop the test. The temperature change resistance is the difference between the temperature before the first peeling and the water temperature. The temperature change resistance of the titanium-based enamel layer in this embodiment is 700°C.
[0130] (8) The bonding strength between the enamel coating and the metal substrate was evaluated by an impact test of the enamel. A 200 g steel ball was used to vertically impact the titanium-based enamel coating in this embodiment from a height of 1 m. The surface showed point-like fractures, with a small area of the shiny metal surface exposed.
[0131] (9) The enamel coating prepared in this example was subjected to a high-speed nanoindentation test. The nanoindentation microhardness distribution of the interface between the TA1 titanium substrate and the enamel was as follows: Fig. 9 As shown. Fig. 9It can be seen that the interface hardness of the titanium-based enamel coating prepared in this embodiment is distributed in a gradient manner, the hardness gradually decreases from the enamel layer to the TA1 titanium substrate, and the depth of the interface layer hardness change is greater than that in Example 1.
[0132] Comparative Example 8:
[0133] Based on Example 7, but with the difference that the enamel frit is mixed and melted by mass percentage, quartz 53.7%, boric acid 14.2%, soda ash 14.1%, lithium carbonate 7.4%, zinc oxide 4.4%, barium carbonate 2.1%, strontium carbonate 3.0%, zirconium quartz powder 1.0% to obtain the enamel frit. The titanium-based enamel coating of Comparative Example 8 was vertically impacted from a height of 1 m, and 2 / 3 of the coating surface area exposed a bright metal surface, and the bonding strength became poor. The temperature resistance of the titanium-based enamel layer of Comparative Example 8 suddenly changed to 425 °C. The nanoindentation microhardness distribution of the interface between the TA1 titanium substrate and the enamel is shown in Fig.10 As shown in FIG. 8 , the interface hardness variation region of the titanium-based enamel coating prepared in Comparative Example 8 becomes wider, that is, the interface thickness increases. Fig.11 It can be seen from the EDS that the diffusion of O at the interface is small. The increase of SiO2 content in enamel promotes the interface reaction between SiO2 and Ti. x Si y The formation of silicide hinders the oxidation of the Ti layer. x Si y It is a porous brittle silicide, and its large accumulation at the interface will reduce the interfacial bonding strength.
[0134] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a titanium-based enamel coating, characterized in that: The steps include: (1) According to the mass percentage, 100% of enamel frit, 6% of clay, 0.15% of nitrite and 35% of water are mixed to obtain enamel glaze slurry; wherein, according to the mass percentage, the enamel frit contains 28-47.7% of quartz, 21.2-46.4% of boric acid, 10.5-13.6% of soda ash, 5.4-6.9% of lithium carbonate, 1.8-3.0% of barium carbonate and 2.6-5.5% of strontium carbonate; wherein the preparation method of the enamel frit comprises the following steps: (1.1) According to mass percentage, 28-47.7% of quartz, 21.2-46.4% of boric acid, 10.5-13.6% of soda ash, 5.4-6.9% of lithium carbonate, 3.8-4.4% of zinc oxide, 1.8-3.0% of barium carbonate, 2.6-5.5% of strontium carbonate and 0.5-1.0% of zirconium quartz powder are mixed to obtain a batch material; (1.2) Melt the batch material in an electric furnace with silicon-molybdenum rods at 1500-1600 °C for 60-120 min. The melted mixture is quenched with water and dried to obtain an enamel frit. (2) pretreating the surface of the TA1 titanium substrate, and then spraying the enamel slurry prepared in step (1) on the surface of the substrate; (3) placing the substrate coated with the enamel slurry obtained in step (2) in an oven at 100-110° C. and drying for 20-30 minutes; (4) After being completely dried, the substrate is placed in a high-temperature furnace at 740-840 °C and fired for 10-15 min to obtain a titanium-based enamel coating with excellent bonding strength and resistance to sudden temperature changes.
2. The method for preparing a titanium-based enamel coating according to claim 1, characterized in that: The enamel slurry is obtained by ball milling process.
3. The method for preparing a titanium-based enamel coating according to claim 1, characterized in that: The pretreatment in step (2) specifically refers to: polishing the surface of the TA1 titanium substrate with 40-mesh sandpaper, then ultrasonically cleaning it with anhydrous ethanol and deionized water for 20 to 40 minutes in sequence, and after cleaning, drying it with compressed air.
4. The method for preparing a titanium-based enamel coating according to claim 1, characterized in that: The thickness of the titanium-based enamel coating prepared in step (4) is 100-115 μm.
5. A titanium-based enamel coating prepared by the method according to any one of claims 1 to 4.
Citation Information
Patent Citations
Hydrogen or hydrogen isotope infiltration resisting vitreous vallation layer for titanium or titanium alloy and preparation method thereof
CN101215710A
Heat-insulating coating material for firing enamel on surface of titanium alloy and preparation method thereof
CN104193173A
Titanium alloy enamel coating material and preparation method thereof
CN105439450A
Enamel coating for titanium alloy and preparation method thereof
CN107601882A
Preparation method of enamel powder-containing heat resistant antioxidative coating for cast iron surface
CN102432178A